Numerical Study on Simulating the Deposition Process of Cold Spray Multi-Particle Al-6061 based on CEL Method - Кун Тан (Mechanics and Advanced Technologies)
Cold spray is a solid-state deposition technique that improves the performance of part surfaces. Most scholars use the CEL framework to simulate the deposition of single particles on the substrate; Single particle depositions cannot fully characterize coating conditions. This article proposes to use the CEL method to simulate the deposition process of cold spray multi-particles on the Al6061 substrate. A multi-particle wrapped model is nested in a deposition model created by CEL to simulate the cold spray multi-particle deposition process. The Euler-Lagrangian method has the characteristics of high accuracy and robustness, and was selected as the method for multi-particle deposition model simulation; The CEL framework is a feasible method to simulate the actual cold spray multi-particle deposition process. The results show that the CEL framework can simulate the deposition of cold sprayed Al6061 multi-particles on the Al6061 substrate, observe the EVF Void value of the coating, and monitor the porosity of the coating after deposition. It is observed that the maximum substrate surface temperature after deposition is 528.2K and is located at the junction of particle and particle impact; By analyzing the temperature change curve of five points collected on the substrate over time, the curve appears multiple inflection points, indicating that heat transfer occurs between the particles and the substrate during the deposition process; the substrate first heats up and then cools down. During the multi-deposition process, the particles undergo plastic deformation and continuously squeeze the coating, thereby achieving interconnection between the particles and the substrate; Mechanical interlocking between particles forms a coating.